Multidrug use positively correlates with high-risk prescriptions in the Japanese elderly: a longitudinal study - Sayaka Arai; Takahiro Ishikawa; Hisaya Kato; Masaya Koshizaka; Yoshio Maezawa; Takako Nakamura; Takaaki Suzuki; Koutaro Yokote; Itsuko Ishii (BMC, 2019)
Abstract Background There is a lack of evidence that multidrug use triggers adverse events. Therefore, the main purpose of this study was to clarify the relationship between the total number of drugs and number of high-risk prescriptions administered to Japanese elderly patients. Methods Using hospital electronic medical records (EMR), we evaluated the prescriptions of outpatients aged 65 years or older. We defined prescriptions of potentially inappropriate medications (PIMs) and overlapping prescription of drugs with the same mechanism of action (DSAs) as high-risk prescriptions. We analyzed the relationship among total number of drugs and high-risk prescriptions. In addition, we performed a secondary research to determine whether the hospitalization rate and concomitant medication contents differ depending on the high-risk prescriptions. Results Data for 13,630 outpatients were analyzed. A significant positive correlation between the numbers of total drugs and PIMs was found. The prescription frequency of individual PIMs rose as the total number of prescription drugs increased. The odds ratio (OR) of overlapping DSAs was significantly higher in patients using 5 or more drugs. In addition, there were significantly more prescriptions of laxatives among patients with overlapping prescriptions of anticholinergic drugs. The use of almost all PIMs was not an independent risk factor for hospitalization; instead, the number of PIMs was an independent risk factor for hospitalization [OR 1.18 (95% CI, 1.12-1.26)]. Conclusions The number of PIMs and overlapping DSAs were high in patients receiving multidrug treatment. To avoid adverse events and hospitalization, it might be useful to review prescriptions and consider the number of PIMs and overlapping DSAs.